2020
DOI: 10.1101/2020.07.13.200865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insecticide resistance status of malaria vectorsAnopheles gambiae s.lof southwest Burkina Faso and residual efficacy of indoor residual spraying with microencapsulated pirimiphos-methyl insecticide

Abstract: The rapid spread of insecticide resistance in malaria vectors and the rebound in malaria cases observed recently in some endemic areas underscore the urgent need to evaluate and deploy new effective control interventions. A randomized control trial was conducted with the aim to investigate the benefit of deploying complementary strategies, including indoor residual spraying (IRS) with pirimiphos-methyl, in addition to long-lasting insecticidal nets (LLINs) in Diébougou, southwest Burkina Faso. We measured the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, the emergence of resistance to the main classes of insecticides used in the treatment of bed nets and in indoor residual spraying (IRS) requires re-thinking the use of these tools and the management of resistance in vectors [2]. Resistance has already been reported in various West African countries including Benin, Burkina Faso, Mali [3][4][5] and particularly in Togo [6,7]. Recent studies showed that the use of synergists and combination of insecticide formulationscan increase the susceptibility of malaria vectors in areas with high pyrethroid resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the emergence of resistance to the main classes of insecticides used in the treatment of bed nets and in indoor residual spraying (IRS) requires re-thinking the use of these tools and the management of resistance in vectors [2]. Resistance has already been reported in various West African countries including Benin, Burkina Faso, Mali [3][4][5] and particularly in Togo [6,7]. Recent studies showed that the use of synergists and combination of insecticide formulationscan increase the susceptibility of malaria vectors in areas with high pyrethroid resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%